2013
DOI: 10.1016/j.ophtha.2013.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia, Hyperopia, and Astigmatism in Non-Hispanic White and Asian Children

Abstract: Purpose To determine the age-, gender- and ethnicity-specific prevalence of myopia, hyperopia and astigmatism in Non-Hispanic White (NHW) and Asian preschool children. Design Population-based cross-sectional study. Participants A population based sample of 1501 NHW children and 1507 Asian children aged 6-72 months from Los Angeles County and Riverside County, California. Methods Eligible children underwent an in-home and in-clinic interview and a comprehensive eye examination including cycloplegic auto-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
115
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 32 publications
14
115
3
1
Order By: Relevance
“…29 These data can reflect that there might be an increase in the prevalence of myopia in school-aged children in Guangzhou. In addition, a prior study in 2012 showed that the prevalence of child myopia in Korea was 22.6%, 8 and a recent study in the United States demonstrated that the prevalence of myopia in non-Hispanic white children was only 1.20% and in Asian children was 3.98%; 30 the prevalence of myopia in these studies were lower than that described in our study. A possible explanation for the variance in the prevalence of myopia in children could be differences in the nature of the samples, in the ethnic backgrounds, in the age, or in the definition of myopia.…”
Section: Discussioncontrasting
confidence: 76%
“…29 These data can reflect that there might be an increase in the prevalence of myopia in school-aged children in Guangzhou. In addition, a prior study in 2012 showed that the prevalence of child myopia in Korea was 22.6%, 8 and a recent study in the United States demonstrated that the prevalence of myopia in non-Hispanic white children was only 1.20% and in Asian children was 3.98%; 30 the prevalence of myopia in these studies were lower than that described in our study. A possible explanation for the variance in the prevalence of myopia in children could be differences in the nature of the samples, in the ethnic backgrounds, in the age, or in the definition of myopia.…”
Section: Discussioncontrasting
confidence: 76%
“…Myopia is generally defined as a spherical refractive error caused by excessive refractive power and/or axial lengthening of the eye, which result in anterior displacement of focus from the retina. 20 In recent epidemiological studies reporting prevalence rates of myopia, although a majority of studies defined myopia as spherical equivalence (SE)r À 0.5 dioptres (D), a wide variety of definitions was adopted for the identification of individuals with myopia: from an SEr À 0.12 D to SEr À 1.0 D. 7,8,[10][11][12] Great variation in methodology, including sampling procedure, cut-off points for definition of age groups, and methods used for measuring refractive error, still exists in recent epidemiological studies on myopia.…”
Section: How Big Is the Problemmentioning
confidence: 99%
“…These studies have confirmed the previous data indicating that prevalence of refractive error varies according to ethnicity and geographic regions. [7][8][9][10][11][12][13][14][15][16][17] Recent epidemiological studies also point to an increase in myopia prevalence over the past half-century. Various environmental factors related to socioeconomic status and lifestyle have been reported, and are widely considered to be possibly responsible for these changes.…”
mentioning
confidence: 99%
“…While these data provide a reference point, they do not provide normative data on axial length increase during childhood. This is due to numerous variables that may contribute to refractive and axial length changes including age of myopia onset [27,31], ethnicity [31][32][33][34][35][36], hours of near work [37], hours of time spent outdoors [38], mode of refractive correction [20,24,39] and parental history of myopia [40]. …”
Section: Axial Length Changes With Other Modes Of Correctionmentioning
confidence: 99%